The Early Carboniferous (Mississippian) ammonoids from the Chebket el Hamra (Jerada Basin, Morocco) - D. Korn; V. Ebbighausen (Fossil Record, 2008)
Five Late Viséan ammonoid assemblages of North Variscan provenance are described from the locality Chebket el Hamra (Jerada Basin, north-eastern Morocco). These assemblages are composed of 27 species of the genera Eoglyphioceras, Girtyoceras, Sulcogirtyoceras, Metadimorphoceras, Goniatites, Arnsbergites, Hibernicoceras, Paraglyphioceras, Lusitanoceras, Sudeticeras, Neoglyphioceras, Lusitanites, Ferganoceras, Praedaraelites, and Pronorites. The new subfamily Arnsbergitinae is described, as well as the thirteen new species Eoglyphioceras minutum n. sp., Girtyoceras ibnkhaldouni n. sp., Metadimorphoceras anguinosum n. sp., Arnsbergites ferrus n. sp., Arnsbergites proiecturus n. sp., Arnsbergites rufus n. sp., Hibernicoceras touissitense n. sp., Hibernicoceras artilobatum n. sp., Paraglyphioceras celeris n. sp., Lusitanoceras zirari n. sp., Sudeticeras ibnbajjahi n. sp., Sudeticeras horoni n. sp., and Pronorites owodenkoi n. sp.doi:10.1002/mmng.200800004